2019
DOI: 10.1136/bcr-2019-229945
|View full text |Cite
|
Sign up to set email alerts
|

Malignant deciduoid mesothelioma: a rare variant of epithelioid mesothelioma

Abstract: We describe a case of a deciduoid mesothelioma, a rare variant of epithelioid mesothelioma, which is associated with a very poor prognosis. A review of the relevant literature is also included. The patient was a man with probable asbestos exposure and presented with classic features of pleural malignancy. Diagnosis was reached with close correlation between clinical, radiological and pathological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We agree that deciduoid cytology needs to be distinguished from carcinomas, but we have recently come across a case of deciduoid pleural mesothelioma which was associated with a very poor response to chemotherapy and a very limited life span in a patient with, initially, excellent performance status. 3 Our literature review revealed that the deciduoid variant is associated with a very poor prognosis, with an approximate 1-year mortality of 68%. Nevertheless, we are well aware that there are no large-scale survival studies for deciduoid pleural mesothelioma because it is a rare entity.…”
Section: To the Editormentioning
confidence: 93%
See 1 more Smart Citation
“…We agree that deciduoid cytology needs to be distinguished from carcinomas, but we have recently come across a case of deciduoid pleural mesothelioma which was associated with a very poor response to chemotherapy and a very limited life span in a patient with, initially, excellent performance status. 3 Our literature review revealed that the deciduoid variant is associated with a very poor prognosis, with an approximate 1-year mortality of 68%. Nevertheless, we are well aware that there are no large-scale survival studies for deciduoid pleural mesothelioma because it is a rare entity.…”
Section: To the Editormentioning
confidence: 93%
“…Reviewing the image in the article, it seemed that this tumor has a high nuclear grade-this becoming increasingly established as an important poor prognostic indicator. [2][3][4][5] Indeed, in one case series involving 21 epithelioid mesotheliomas with deciduoid cytology, 6 the cases could be prognostically separated through their nuclear features. Furthermore, a recent metaanalysis noted that there was no obvious difference overall between epithelioid mesotheliomas with deciduoid cellular structure and those without.…”
Section: In Replymentioning
confidence: 99%